Sustainable development and digitalization - the main trends in construction development - Skakun , V (Ways to Improve Construction Efficiency, 2022)
The article examines the key trends in the transformation of the construction industry in the context of sustainable development and digitalization, which are the dominant directions of modern economic, social and technological progress. It is substantiated that sustainable development in construction is not only environmental responsibility, but also a comprehensive strategy of long-term efficiency, which includes the rational use of resources, reducing CO₂ emissions, increasing energy efficiency and taking into account social factors in the design, construction and operation of real estate. The authors emphasize that in the context of growing environmental risks and tightening regulatory regulation, it is a sustainable approach to design and construction that becomes a competitive advantage for development companies.Digitalization is considered a powerful driver of innovation in the construction sector, which provides a fundamental change in the methods of planning, implementation and control of projects. The modern digital technologies that are most actively implemented in construction are analyzed: BIM modeling (Building Information Modeling), ERP resource management systems, digital platforms for real-time process monitoring, as well as object life cycle management systems (LCC). It is emphasized that it is the integration of digital solutions that allows you to optimize costs, reduce project risks, and improve the quality and safety of objects.The article identifies the synergistic effect of combining sustainable development and digitalization: digital technologies act as a tool for implementing the principles of sustainable construction, ensuring transparency, controllability, and predictability of development processes. Examples of world practice of digital-ecological transformations in construction are considered, in particular, the introduction of digital building passports, digital carbon footprint control, and automated energy management systems.It is concluded that the transition of the construction industry to a sustainable development paradigm combined with digital transformation is not just a trend, but an imperative for maintaining competitiveness, increasing resilience to external threats, and forming a new type of construction environment — environmentally neutral, adaptive, and intelligent.